A retrospective analysis of project undertaken to curtail the number of post-mortem examinations based on Section 174 CrPC with respect to burn injuries - Chaphalkar, Kavita N; Khandekar, Indrajit; Tirpude, B H (Journal of Indian Academy of Forensic Medicine, 2020)
A project was implemented at MGIMS, Sevagram from 2016 onwards based on Section 174 CrPC to curtail the avoidable cases of post-mortem examination without violating the law. Under this project, police were directed to use modified formats for inquiry or investigation into the cause of deaths i.e., commonly known as inquest. Modified inquest format mandates to mention the cause of death if it is certified by the treating doctor and also the reason/s for forwarding the case for post-mortem examination as per subclauses under Section 174(3) CrPC. The aim of current study was to analyse outcome of this project with respect to number of post-mortem examinations in cases of burn injuries. Data of all cases of burn admitted and died while under treatment at the hospital during period from 2013 to Sep’ 2018 was gathered from ’Hospital Information System’ and Computerized Autopsy reports and retrospectively analysed using Microsoft Office 2007 excel worksheet. There were 287 deaths due to burn injuries during the study period. Out of these 287 deaths, 178 cases were during the period 2013-2015. Out of these 178 cases, 176 (98.88%, n= 178) cases were forwarded by police for post-mortem examination. Out of 287 deaths, 109 cases were during the period 2016-2018 with number of cases forwarded by police for post